2019
DOI: 10.3748/wjg.v25.i7.859
|View full text |Cite
|
Sign up to set email alerts
|

Δ4-3-oxosteroid-5β-reductase deficiency: Responses to oral bile acid therapy and long-term outcomes

Abstract: BACKGROUND Disorders of primary bile acid synthesis may be life-threatening if undiagnosed, or not treated with primary bile acid replacement therapy. To date, there are few reports on the management and follow-up of patients with Δ4-3-oxosteroid 5β-reductase (AKR1D1) deficiency. We hypothesized that a retrospective analysis of the responses to oral bile acid replacement therapy with chenodeoxycholic acid (CDCA) in patients with this bile acid synthesis disorder will increase our understanding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…The c.797G>A (p.Arg266Gln) homozygous mutation in the AKR1D1 gene found in the first two patients in this study has been reported in several studies [7,18] . However, the homozygous mutation c.155T>C (p.Ile52Thr) in the AKR1D1 gene identified in patient 3 was a thoroughly novel variant [19] .…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The c.797G>A (p.Arg266Gln) homozygous mutation in the AKR1D1 gene found in the first two patients in this study has been reported in several studies [7,18] . However, the homozygous mutation c.155T>C (p.Ile52Thr) in the AKR1D1 gene identified in patient 3 was a thoroughly novel variant [19] .…”
Section: Discussionsupporting
confidence: 54%
“…[17] The c.797G>A (p.Arg266Gln) homozygous mutation in the AKR1D1 gene found in the first two patients in this study has been reported in several studies. [7,18] However, the homozygous mutation c.155T>C (p.Ile52Thr) in the AKR1D1 gene identified in patient 3 was a thoroughly novel variant. [19] Thus, for the first time, we present this rare disease among the Vietnamese population and describe a novel mutation c.155 T>C, Ile to Thr substitution, which we added to the archive of AKR1D1 variants.…”
Section: Discussionmentioning
confidence: 99%
“…[17,18,24] In Japan, CDCA is used instead of CA for treatment of BASD, since the latter is not available for clinical use in Japan; the same is true for China. [25] We have obtained a reliable therapeutic effect from CDCA, and believe that a low dose of CDCA (5 to 10 mg/kg/day) can obtain sufficient benefit. [10,13] Low doses are particularly important because CDCA is more hepatotoxic than CA.…”
Section: Discussionmentioning
confidence: 87%
“…However, administration of cholic acid or chenodeoxycholic acid suppresses endogenous hepatic bile acid synthesis (14,44,45), which is already low in these patients. In contrast, UDCA and its glycine conjugate can act as a farnesoid X‐receptor antagonist in humans (15,45) to stimulate endogenous hepatic bile acid synthesis (45,46), which is predicted to be beneficial for promoting intestinal lipid absorption.…”
Section: Discussionmentioning
confidence: 99%
“…After a hospital stay of 4.5 months and recovery from rickets, the patient continued with mixed intravenous and partial enteral nutrition (gluten-and cow milk-free, enriched for medium-chain fatty acids). At 2 years of age, UDCA treatment was initiated (20 mg/kg/d), given its safety profile, ability to improve liver function, and potential to promote fat absorption (12)(13)(14)(15). Parenteral nutrition was suspended, she transitioned to full oral nutrition, and solid stools were noted.…”
Section: Clinical Descriptionmentioning
confidence: 99%